2021
DOI: 10.1186/s12888-021-03301-3
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic correlates of public stigma about mental illness: a population study on Hong Kong’s Chinese population

Abstract: Background Individuals with psychiatric disorders are often unwilling to seek help or often follow treatment regimens, fearing public stigma. This study identified the sociodemographic correlates of public stigma while accounting for mental health literacy and life satisfaction. Methods This study analysed data for 1514 individuals who participated in a population-based random telephone survey conducted in 2018. Sociodemographic characteristics inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
2
11
0
1
Order By: Relevance
“…A recent study examined the link between health literacy skills and diabetes risk among non-diabetic adults in the German population concluding that low health literacy was associated with behaviors that increase the risk of type-2 diabetes such as smoking, inactive lifestyle and poor dietary habits [ 60 ]. Similar correlations have been found for low health literacy and another diseases, including mental illness [ 61 ], cancer screening [ 62 ] or the COVID-19 pandemic [ 63 ], among others. Education level, socioeconomic status and physical limitations to perform routine activities (e.g.…”
Section: Ethical Implications Of Epigenetic-predictive Biomarkerssupporting
confidence: 75%
“…A recent study examined the link between health literacy skills and diabetes risk among non-diabetic adults in the German population concluding that low health literacy was associated with behaviors that increase the risk of type-2 diabetes such as smoking, inactive lifestyle and poor dietary habits [ 60 ]. Similar correlations have been found for low health literacy and another diseases, including mental illness [ 61 ], cancer screening [ 62 ] or the COVID-19 pandemic [ 63 ], among others. Education level, socioeconomic status and physical limitations to perform routine activities (e.g.…”
Section: Ethical Implications Of Epigenetic-predictive Biomarkerssupporting
confidence: 75%
“…People with higher education were more likely to seek help in this research, which is in line with the previous study ( 48 ). This can be explained by stigmatization: people with higher education were less stigmatized ( 49 ). Thus, they were often willing to admit having mental health problems and seek help.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current study, the stigma of depression is pervasive among the majority of participants across all age groups. Here lies the danger of stigma in reaching all age groups and not excluding any age group, According to findings from another study, stigma against mental illness is more prevalent among those who are older [13]The study found that there is a significant difference at 0.05 in the development of stigma and gender, with differences in favor of females, meaning that females have a higher stigma than males. This finding is in line with the study by Suen et al [14] which suggested a connection between the female gender and higher levels of stigma.…”
Section: Discussionmentioning
confidence: 98%